REAKSI PASAR TERHADAP PENGUMUMAN RIGHT ISSUE DI BURSA EFEK INDONESIA - NIRMALA .; NININ NON AYU SALIMAH (Program Studi Magister Manajemen FE Unsri, 2015)
This research aimed to examine the differences of the market reactions before-after announcement of right issue showing by the present of mean difference of trading volume activity and average abnormal return. This research uses event study. The population is firms listed on Indonesian Stock Exchange and publishing right issue in 2009-2013. The number of sample is 49 firms with purposive sampling by giving the criteria which are announcing the policy of right issue, not doing another corporate action during the period of research and owning the complete data needed. The technique to analyze data using paired sample test to examine hypothesis after counting the trading volume activity and average abnormal return and doing normality examination. This research results in no difference of market reactions between before-after announcement of right issue showing by no difference average of trading volume activity and average abnormal return